KESANTUNAN BERBAHASA DALAM KOMENTAR PEMBACA BERITA - Slamet Triyadi; Enung Nurhayati (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2021)
The purpose of making this thesis is to determine the obedience and violations of politeness according to Leech's theory, in addition to knowing the causes of language violations according to the Pranowo theory in chaer, and to describe the implications of language politeness on learning Indonesian. The amount of data to be analyzed is four different news themes, with the total number of comets being two hundred and one comments. In this study, the method used is a qualitative method that produces descriptive data. In data collection, the authors used the listening technique, namely speaking free and followed by note-taking techniques. Furthermore, it is described by providing analysis and then given the final conclusion, and this language politeness can be implicated as teaching material for junior high school teachers in Indonesian language learning. The results of this study show that from all data one, two, three and four that comply with Leech's politeness, eighty-nine comments are obtained, and from all data one, two, three and four that violate Leech's politeness, sixty-eight comments data are obtained. Meanwhile, in general, the causes of violations of language politeness are two direct critical comments with harsh words, four comments that encourage the speaker's emotional feeling, one speech is protective of the opinion, one comment is deliberately accusing the interlocutor, two comments deliberatelycornering the speech partner. Language politeness can be implicated in junior high school teachers in Indonesian language learning, which is related to the response text material, this response text material is found in chapter four in grade nine odd semesters. Keywords: Principles of Obedience and Violation of Political, Causes of Violation of of civility, Implication Form.